-3(5-2x)=4x+1

Simple and best practice solution for -3(5-2x)=4x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(5-2x)=4x+1 equation:


Simplifying
-3(5 + -2x) = 4x + 1
(5 * -3 + -2x * -3) = 4x + 1
(-15 + 6x) = 4x + 1

Reorder the terms:
-15 + 6x = 1 + 4x

Solving
-15 + 6x = 1 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-15 + 6x + -4x = 1 + 4x + -4x

Combine like terms: 6x + -4x = 2x
-15 + 2x = 1 + 4x + -4x

Combine like terms: 4x + -4x = 0
-15 + 2x = 1 + 0
-15 + 2x = 1

Add '15' to each side of the equation.
-15 + 15 + 2x = 1 + 15

Combine like terms: -15 + 15 = 0
0 + 2x = 1 + 15
2x = 1 + 15

Combine like terms: 1 + 15 = 16
2x = 16

Divide each side by '2'.
x = 8

Simplifying
x = 8

See similar equations:

| 4(x-6)=2(2x-12) | | 2x+3(7x-5)=192 | | x+23=35 | | 1b-73=-1b-3 | | 1+n=2n+9 | | 15b+2=-28 | | 5(2x+5)+3x=-74 | | 9+4(7x+8)=-7 | | 4(x-1)-2x=9 | | x^2(x-5)=6x | | 12+3b=90 | | 12r+34=6r-(-9) | | 11x-8x-7=35 | | B-73=-b-3 | | %*30=48 | | x^4+11x^2+36=0 | | y+5=x(x+2) | | 2.5x+4.3x-5=0 | | 6x-8+11=8x-11+11 | | 8w+8-2-2w= | | 4y(-2d-3)=12 | | -4(-4x+5)=-10x-6 | | 4x+8=4.75x+15 | | -13=-4+6x | | 5v-5v=1-2 | | 7x-1=-15 | | 25*24000= | | S+31=15 | | 5v-5v= | | -6a-30=-4(5+2a) | | 8x^2+9x+h=0 | | 5(2p+5)=5p+12.5 |

Equations solver categories